The Impact of Inflation and Operating Cycle on the Corporate Cash Holdings in South-East Europe - Naumoski, Aleksandar; Juhasz, Peter (Faculty of Organizational Sciences, University of Belgrade, 2018)
Research Question: This paper investigates the influence of the inflation and operating cycle on the corporate cash holdings. Motivation: In an early study, Keynes (1936) provides a theoretical foundation for determining the optimal cash level as a balance of costs and benefits of cash holdings. However, the optimal corporate cash amount is not only dependent on many company-specific factors (Opler et al., 1999), but it is also associated both with the corporate governance structure and the institutional and macroeconomic environment (Ozkan and Ozkan, 2004). Anand et al. (2018) confirmed the impact of a set of macroeconomic factors, but recent studies distinguished inflation as a critical factor of the changes of the company cash holdings (Curtis et al., 2017). Idea: The main idea of the paper is to examine whether inflation as a crucial macroeconomic factor and operating cycle as a vital microeconomic factor have substantial influence on the corporate cash holdings, and which direction this impact may take. Data: We used company financial data from a sample of 868 publicly traded firms from ten South-East European countries between the years of 2006 and 2015, obtained from the Thomson Reuters Datastream database. Tools: We apply a balanced panel regression model involving the yearly change of the cash ratio as a dependent variable, and country CPI, operating cycle and other firm-specific control variables as explanatory variables. Findings: Results confirm that both the inflation and operating cycle have a substantial influence on the change of the corporate cash holdings. The relationship of the change in cash and the inflation is non-linear and best described by a U-shaped curve. At the same time, there is a straight linear relationship between the change in cash holdings and operating cycle. Moreover, we found that the changes in the corporate cash holdings are positively related with the size of the company, the operating cash flow and the capital expenditures, but inversely related with the change of the net working capital and the change of short and long-term debt. Contribution: This paper reveals the effect of macro-control policies on corporate cash holdings, and most importantly, it provides a reference for corporate managers to optimise the allocation of resources based on changes in the macro-financial environment and their own financial circumstances.
Keywords: CPI, liquidity, working capital, operating cycle, panel regression, corporate cash holdings